The Influence of Psychocurative on Cortisol Level, Anxiety, and Quality of Life in Advanced Stage Cervical Cancer Patients - Soetrisno, Soetrisno; Mulyani, Sri; Nurinasari, Hafi; Nurinasari, Hafi; Budi, Erindra (Folia Medica Indonesiana, 2019)
Every year, there are 500.000 new cases and more than 250.000 deaths caused by cervical cancerworldwide. Cervical cancer patients faced physical and psychological problems several times that it activate stress mechanism such as hypothalamus-pituitary-adrenal (HPA) axis. These recurrent activations caused HPA axis disruption and adverse clinical effects. Several symptoms of endocrine stress response are the change of circadian cortisol rhythm. Cortisol is known as a stress hormone that involves an organism's response to stress and anxiety that influence the quality of life. This research aims to analyze the differences among serum cortisol level, anxiety, and quality of life in cervical cancer patients before and after psychocurative intervention in obstetrics and gynecology wards and polyclinic in RSUD Dr. Moewardi Surakarta. This research is an experimental double-blind randomized controlled clinical trial pre-test post-test group design study. The subjects were advance stage (IIB-IV)cervical cancer patients. The subjects were randomly chosen into fifteen subjects that given standard therapy and psychocurative, while the other fifteen subjects as a control only got standard therapy. Data were obtained from measurement of serum cortisol level, anxiety questionnaire DASS 42 and WHO quality of life questionnaire. Data were analyzed using SPSS 21 using difference test. The difference mean test result of cortisol serum level, anxiety, quality of life from the controlled group and uncontrolled group showed a significant difference (p < 0.05). In conclusion, psychocurative is significant to reduce cortisol level, anxiety, and improve the quality of life in advanced stage cervical cancer patients.